Constructing Eco-Islamic University Model: Strategies for Pesantren-Based Higher Education - Rahmawati, Nur Laila; Asnawi, Asnawi; Anis Afifah; Rahmawati, Fatya Nia; Eryul Mufidah (Berkala Ilmiah Pendidikan, 2026)
Bojonegoro faces a critical paradox: it serves as a national energy and extractive-industry hub, yet remains highly vulnerable to ecological disasters such as floods, landslides, and droughts. Despite this alarming condition, Pesantren-based higher education institutions which act as the moral and intellectual foundation for local communities currently lack a comprehensive educational model that integrates Islamic values with a strategic responsiveness to the environmental crises caused by these extractive industries. Therefore, this study aims to construct the "Attanwir Eco-Islamic University Model" as a systematic, preventive, and educational strategy to address these local ecological challenges. Employing a qualitative exploratory case study design at Institut Attanwir Bojonegoro, data were collected through in-depth interviews, participant observations, and documentation. The data were analyzed interactively using the Miles, Huberman, and Saldaña model, comprising data condensation, display, and conclusion drawing. The findings propose a robust framework built upon three integrated pillars. First, a Philosophical Foundation rooted in "Feminine Theology" (emphasizing the compassionate attributes of Ar-Rahman and Ar-Rahim) to counter anthropocentric exploitation. Second, an Academic Framework that embeds local issues, such as oil waste and teak forest conservation, directly into the Environmental Jurisprudence (Fiqh al-Bi'ah) curriculum. Third, a Social System that institutionalizes a "green lifestyle" through practices such as plastic fasting and eco-wudhu. The study concludes that this Eco-Islamic model is vital for transforming universities into moral beacons, ultimately producing graduates who are not only intellectually competent but also agents of change, possessing profound ecological piety to advocate for communities in vulnerable industrial zones.